2015
DOI: 10.1056/nejmoa1507198
|View full text |Cite
|
Sign up to set email alerts
|

A Trial of Early Antiretrovirals and Isoniazid Preventive Therapy in Africa

Abstract: BACKGROUND: In sub-Saharan Africa, the burden of human immunodeficiency virus (HIV)-associated tuberculosis is high. We conducted a trial with a 2-by-2 factorial design to assess the benefits of early antiretroviral therapy (ART), 6-month isoniazid preventive therapy (IPT), or both among HIV-infected adults with high CD4+ cell counts in Ivory Coast. METHODS: We included participants who had HIV type 1 infection and a CD4+ count of less than 800 cells per cubic millimeter and who met no criteria for starting AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

23
447
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,022 publications
(489 citation statements)
references
References 38 publications
23
447
1
1
Order By: Relevance
“…Since then, the scientific rationale for TasP has expanded. In 2015, two randomized clinical trials showed that initiating ART as soon as possible after HIV diagnosis (regardless of disease stage) also yielded strong clinical benefits to the individual 7, 8.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the scientific rationale for TasP has expanded. In 2015, two randomized clinical trials showed that initiating ART as soon as possible after HIV diagnosis (regardless of disease stage) also yielded strong clinical benefits to the individual 7, 8.…”
Section: Introductionmentioning
confidence: 99%
“…Early antiretroviral treatment (ART) of HIV‐positive patients has been shown to prevent transmission of HIV 1, in addition to individual benefits in terms of reducing morbidity and mortality 2, 3. The universal test and treat (UTT) strategy was developed by extending this idea to the population level under the hypothesis that HIV testing of all adult members of a community, followed by immediate ART initiation of nearly all HIV‐positive individuals, regardless of immunological or clinical staging, will prevent onward transmission and reduce HIV incidence in the community.…”
Section: Introductionmentioning
confidence: 99%
“…This recommendation reversed earlier guidelines that limited treatment to patients with lower CD4 counts or severe illness 1. Although expanding eligibility is expected to reduce morbidity, mortality and transmission among patients with high CD4 2, 3, 4, 5, 6, 7, 8, it is possible that a large influx of newly eligible patients in a resource‐limited health system could crowd out sicker patients and reduce quality of care for all patients. As of September 2016, South Africa has joined three other countries in sub‐Saharan Africa in adopting the WHO ‘test‐and‐treat’ policy 9, 10, and additional resource‐limited countries are also considering expanding eligibility 11, 12.…”
Section: Introductionmentioning
confidence: 99%